UPAYA MENINGKATKAN KESEGARAN JASMANI MELALUI PENDEKATAN BERMAIN DALAM PEMBELAJARAN PENDIDIKAN JASMANI KELAS XII-2 SMA NEGERI 7 KEDIRI - Prasetyo Utomo; Budiman Agung Pratam; Miftahkodin (JOURNAL SAINS STUDENT RESEARCH, 2025)
Physical Education is a learning process through physical activities that is designed to improve physical fitness, develop motor skills, knowledge, healthy living behaviors, active, sportsmanship, and emotional intelligence. The learning experiences presented will help students understand why humans move and how to do safe, efficient and effective movements. This study aims the existence of a problem-action planaction-evaluation and reflection action. The subjects used were all students of KELAS XII-2 SMA Negeri 7Kediri in the 2024/2025 academic year as many as 32 students. Based on the results of the study it can be concluded that: (1) The results of this study indicate that with the learning model with the approach to play in learning there is an impact of changes in motivation and at the same time a student's physical fitness level. This is because they can learn while playing. With this activity students' cognitive, affective and psychomotor abilities can develop